Driving customer loyalty: Mediating effect of customer satisfaction on service quality and brand image - Sekarwangi, Ida Ayu Mirah; Ekawati, Ni Wayan (International research journal of management, IT and social sciences, 2025)
This study investigated the critical roles of service quality and brand image in driving customer loyalty, specifically examining how customer satisfaction mediates these relationships among Indihome users in Denpasar. Grounded in the Stimulus-Organism-Response (S-O-R) theory, this research explores how service quality and brand image, as external stimuli, influence internal consumer satisfaction to foster loyalty. A quantitative approach was employed, collecting data through an online survey from 250 Indihome consumers in Denpasar. Data analysis utilized Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings confirm that service quality and brand image both positively and significantly influence customer loyalty directly. Additionally, both service quality and brand image positively and significantly impact customer satisfaction. Crucially, customer satisfaction was found to directly and positively affect customer loyalty, and it partially mediates the relationships between service quality, brand image and customer loyalty. These results highlight that customer satisfaction is a vital internal response, significantly amplifying how service quality and brand image translate into stronger customer loyalty.